Walking through doorways causes forgetting: recall. Issue 10 (26th November 2018) - Pettijohn, Kyle A.; Radvansky, Gabriel A.
ABSTRACT: The aim of the current study was to explore how the location updating effect is affected when people are tested using recall rather than recognition, which is what has been done in prior work. Differences in the memory processes involved with these two tasks lead to predictions for two different patterns of data. In Experiment 1, memory was tested by having participants recall the single object they were carrying or had just put down, whereas in Experiment 2, people sometimes needed to recall both objects. It was found that, unlike recognition test performance, a similar location updating effect was found for both Associated (what was currently being carried) and Dissociated (what was recently set down) objects. Moreover, when both objects were correctly recalled, there was a bias to remember them in the order that they were encountered. Finally, if only one object was correctly recalled, it was the Associated object that was currently being carried. Overall, these results are consistent with the Event Horizon Model of event cognition.